2020
DOI: 10.1177/0022242920925038
|View full text |Cite
|
Sign up to set email alerts
|

Providers Versus Platforms: Marketing Communications in the Sharing Economy

Abstract: Peer-to-peer (P2P) business models have become increasingly prevalent in the marketplace. However, little is known about what factors influence consumer perceptions of purchases from firms using these models. The authors propose that features inherent to the P2P model lead consumers to perceive high provider–firm independence, where providers are viewed as relatively independent from the platform on which they offer goods/services. Across a series of studies, the authors show that when P2P brands use provider-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…For example, Bhagwat et al’s (2020) observations of corporate social activism by brands and marketers’ worries about the financial implications of such actions led them to study this concern as a research question. Similarly, Costello and Reczek (2020) observed that some sharing platforms focused on their providers while others referred to their own platforms in their marketing communications. This observation led to an investigation into the effectiveness of these different approaches and underlying mechanisms.…”
Section: Bringing Ecological Value To the Research Problemmentioning
confidence: 97%
“…For example, Bhagwat et al’s (2020) observations of corporate social activism by brands and marketers’ worries about the financial implications of such actions led them to study this concern as a research question. Similarly, Costello and Reczek (2020) observed that some sharing platforms focused on their providers while others referred to their own platforms in their marketing communications. This observation led to an investigation into the effectiveness of these different approaches and underlying mechanisms.…”
Section: Bringing Ecological Value To the Research Problemmentioning
confidence: 97%
“…Although in most buying situations buyers focus on economic motives (e.g., paying a low price), specific business models and transaction types exist that uniquely activate both economic and social payment motives. For example, recent research on peer-to-peer (P2P) businesses shows that provider-focused (vs. platform-focused) marketing communications lead consumers to think about their purchases from the provider’s (vs. platform’s) perspective, which increases their willingness to pay (Costello and Reczek 2020). Similarly, we posit that in PWYW transactions, buyers may be socially motivated and consider what is appropriate to the seller in determining what to pay.…”
Section: Background Literaturementioning
confidence: 99%
“…With effect from 16 March 2020 from 6.00 am, all retail shops and all retail establishments providing services were closed for a period of 14 days, except forshops offering food, meat, bread and pastry, fruit and vegetables, newspapers and also pharmacies, drugstores, feed stores for animals and operations of online shops [9].However, SHS Web of Conferences 9 2, 010 (2021) Globalization and its Socio-Economic Consequences 2020 this situation eventually lasted much longer, the first wave of looseningthe restrictions did not come until April 22, 2020.For this time, the Public Health Authority in Slovakia proposed measures in commercial operations that persist even after the emergency: customers can only enter stores with their nose and mouth covered; they are obliged to use hand sanitizer or disposable gloves; one customer per 10 square meters is recommended, with 2 meter intervals between customers; the trader should ensure frequent ventilation of the premises and regular disinfection of the contact surfaces [10,11,12].…”
Section: Resultsmentioning
confidence: 99%